Effect of exhaustive incremental treadmill effort on force generation repeatability in biathlete - Jastrzebska, A. D.; Blacha, R. (Journal of Motor Behavior, 2014)
The authors examined how force generation repeatability changes as the result of incremental maximal test to volitional exhaustion by well-trained (VO2/kg [mL·kg-1·min-1] 62.55 ± 5.27) individuals. 13 young biathletes (18.9 ± 1.7 years) performed isometric maximum voluntary contraction (IMVC) and submaximal targeted (98N) pushes against the force transducers by arms: elbow extension (EE), elbow flexion (EF) and legs: knee extensions (KE) in pre- and posttest conditions after incremental exhaustive test performed on treadmill. IMVC did not differ significantly between pre and posttest conditions for upper and statistically decrease in lower extremities measurements (p <.01). The mean force of 10 submaximal targeted force productions (Fmean; N) is similar for pre- and posttest measurements. Standard deviation of Fmean(Fsd; N) and coefficient variation (CV;%) decrease statistically in elbows flexionp <.02 but not extension. The reduction of force repetition accuracy in left knee extension was noticed (p <.01). The fatigue induced by incremental running test decreases a magnitude of force production variability in specifically trained muscle groups in biathletes.